2005
DOI: 10.1063/1.1896388
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of a Dirac operator in the chiral quark soliton model

Abstract: We consider a Dirac operator H acting in the Hilbert space L 2 ͑R 3 ; C 4 ͒ C 2 , which describes a Hamiltonian of the chiral quark soliton model in nuclear physics. The mass term of H is a matrix-valued function formed out of a function F : R 3 → R, called a profile function, and a vector field n on R 3 , which fixes pointwise a direction in the isospin space of the pion. We first show that, under suitable conditions, H may be regarded as a generator of a supersymmetry. In this case, the spectra of H are symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…From this point of view, it would be interesting to investigate if the Hamiltonian of the present model has supersymmetry. Indeed, it was shown that the Hamiltonian of the CQS model as well as that of the GCQS model has supersymmetry [3,4]. In this section we see that a supersymmetric structure similar to that of the CQS (GCQS) model exists in our model.…”
Section: =1supporting
confidence: 55%
See 4 more Smart Citations
“…From this point of view, it would be interesting to investigate if the Hamiltonian of the present model has supersymmetry. Indeed, it was shown that the Hamiltonian of the CQS model as well as that of the GCQS model has supersymmetry [3,4]. In this section we see that a supersymmetric structure similar to that of the CQS (GCQS) model exists in our model.…”
Section: =1supporting
confidence: 55%
“…In the papers [3,4], it was shown that, under a suitable condition, the Hamiltonian of the CQS (GCQS) model is unitarily transformed to a Dirac operator which is simpler in a sense. In this section, we show that those structures are unified into a simple general structure.…”
Section: Unitary Equivalence To a Gauge Theoretic Dirac Operator And mentioning
confidence: 99%
See 3 more Smart Citations